Dette nummers samlede anmeldelser - Wang, Cancan; Bao, Hongwei; Christensen, Hilda Rømer; Siim, Birte (Kvinder, Køn & Forskning, 2015)
Leta Hong Fincher: Leftover Women: The Resurgence of Gender Inequality in China. Zed Books Ldt, 2014Engebretsen, Elisabeth L.: Queer Women in Urban China: An Ethnography. New York and London: Routledge, 2014Jung Chang: Empress Dowager Cixi. The concubine who launched modern China. Alfred A. Knops. New York, 2013Nancy Fraser: Fortunes of Feminism. From State-Managed Capitalism to Neoliberal Crisis, Verso. London – New York. 2013